Natural killer cells require monocytic Gr-1+/CD11b+ myeloid cells to eradicate orthotopically engrafted glioma cells. (2nd June 2016) - Baker, Gregory J.; Chockley, Peter; Zamler, Daniel; Castro, Maria G.; Lowenstein, Pedro R.
ABSTRACT: Malignant gliomas are resistant to natural killer (NK) cell immune surveillance. However, the mechanisms used by these cancers to suppress antitumor NK cell activity remain poorly understood. We have recently reported on a novel mechanism of innate immune evasion characterized by the overexpression of the carbohydrate-binding protein galectin-1 by both mouse and rat malignant glioma. Here, we investigate the cytokine profile of galectin-1-deficient GL26 cells and describe the process by which these tumors are targeted by the early innate immune system in RAG1 −/− and C57BL/6J mice. Our data reveal that galectin-1 knockdown in GL26 cells heightens their inflammatory status leading to the rapid recruitment of Gr-1 + /CD11b + myeloid cells and NK1.1 + NK cells into the brain tumor microenvironment, culminating in tumor clearance. We show that immunodepletion of Gr-1 + myeloid cells in RAG1 −/− mice permits the growth of galectin-1-deficient glioma despite the presence of NK cells, thus demonstrating an essential role for myeloid cells in the clearance of galectin-1-deficient glioma. Further characterization of tumor-infiltrating Gr-1 + /CD11b + cells reveals that these cells also express CCR2 and Ly-6C, markers consistent with inflammatory monocytes. Our results demonstrate that Gr-1 + /CD11b + myeloid cells, often referred to as myeloid-derived suppressor cells (MDSCs), are required for antitumor NK cell activity against galectin-1-deficient GL26 glioma. We conclude that glioma-derived galectin-1 represents an important factor in dictating the phenotypic behavior of monocytic Gr-1 + /CD11b + myeloid cells. Galectin-1 suppression may be a valuable treatment approach for clinical glioma by promoting their innate immune-mediated recognition and clearance through the concerted effort of innate myeloid and lymphoid cell lineages.